Beyond antidoping and harm minimisation: a stakeholder-corporate social responsibility approach to drug control for sport - Mazanov, Jason (Journal of medical ethics, 2016)
Debate about the ethics of drug control in sport has largely focused on arguing the relative merits of the existing antidoping policy or the adoption of a health-based harm minimisation approach. A number of ethical challenges arising from antidoping have been identified, and a number of, as yet, unanswered questions remain for the maturing ethics of applying harm minimisation principles to drug control for sport. This paper introduces a ‘third approach’ to the debate, examining some implications of applying a stakeholder theory of corporate social responsibility (CSR) to the issue of doping in sport. The introduction of the stakeholder-CSR model creates an opportunity to challenge the two dominant schools by enabling a different perspective to contribute to the development of an ethically robust drug control for sport.